Transcriptome analysis of medaka embryonic eye and ocular organoids [data] - Stahl, Elin; Delgado-Toscano, Miguel Angel; Saravanan, Ishwariya; Paneva, Anastasija; Wittbrodt, Joachim; Zilova, Lucie (Universität, 2026)
The dataset has been generated in order to assess the temporal dynamics of lens-specific gene expression in ocular organoids and embryonic eye. Bulk RNA sequencing of total RNA from medaka fish (O. latipes) embryonic eye and medaka fish - derived ocular organoids at day 0, day 1, day 2, day 3 and day 4 of development. For total RNA sequencing we extracted RNA from whole organoids (composed of both lens and retina), the anterior part of day 1 and 2 embryos (dissected right behind optic vesicles or optic cups), and dissected eyes of 3 dpf and 4 dpf embryos. Samples were prepared in three replicates (indicated as samples S1, S2, and S3). Considering 3 h delay in organoid development with the respect to embryonic development (Zilova et al., 2021), organoids were collected for RNA isolation 3 h later than the embryonic tissue. Total RNA was isolated using Direct-zol RNA Microprep (Zymoresearch, Cat#:R2060) according to the manufacture protocol. Library preparation was performed with the NEBNext Ultra II RNA Library Prep Kit for Illumina with NEBNext Poly A Selection Kit and NEBNext Multiplex Oligos with UMI. Input RNA was quantified with the Qubit BR RNA assay, and qualified on the Agilent Tapestation (RNA Assay), libraries were quantified with the Qubit DNA HS Assay, and qualified on the Agilent Tapestion (D1000 Assay). Libraries were sequenced on the Illumina NextSeq 550 Sequencer. Library preparation and sequencing was performed by CCTP Deep Sequencing Facility of Heidelberg University. Samples are named as embryo_d0_S1 (refer to embryo sample from day 0, replicate sample 1) or lens_organoid_d1_S2 (refer to ocular organoid sample at day 1, replicate sample 2). Libraries were prepared and sequenced in two experiments. One containing embryo samples embryo_d1, embryo_d2, embryo_d3, embryo_d4 and second containing embryo_d0 and organoid samples lens_organoid_d1, lens_organoid_d2, lens_organoid_d3 and lens_organoid_d4. To provide the internal reference and comparison of two experiments, RNA samples from embryo_d2_S2 and embryo_d4_S3 from the first experiment were used for library preparation and sequencing in second sequencing experiment (referred to as embryo_d2_S2_2 and embryo_d4_S3_2). This dataset serves as supplemental information to the manuscript entitled Inverted Assembly of the Lens Within Ocular Organoids Reveals Alternate Paths to Ocular Morphogenesis. doi: https://doi.org/10.1101/2025.04.17.649366.
Gefördert durch: Deutsche Forschungsgemeinschaft: EXC-2082/1-390761711
Gesehen am 16.02.2026
Keywords: Forschungsdaten; Datenbank